2009
DOI: 10.1097/aog.0b013e3181af6abd
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating Vaginal Repair in Rats Through Skeletal Muscle–Derived Stem Cells Seeded on Small Intestinal Submucosal Scaffolds

Abstract: OBJECTIVES Grafts are used for vaginal repair after prolapse, but their use to carry stem cells to regenerate vaginal tissue has not been reported. In this study, we investigated whether 1) muscle-derived stem cells (MDSC) grown on small intestinal submucosa (SIS) generate smooth-muscle cells (SMC) in vitro and upon implantation in a rat model of vaginal defects; 2) express markers applicable to the in-vivo detection of vaginal endogenous stem cells; and 3) stimulate the repair of the vagina. METHODS Mouse M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 27 publications
4
36
1
4
Order By: Relevance
“…This study highlights detailed differences in specific tensile properties between cellseeded and non-cell-seeded scaffolds, with enhanced collagen organization for scaffolds implanted with eMSCs. In agreement with our findings, others have found increased total collagen content for cell-seeded scaffolds following implantation [12,13], with enhanced stimulation of tissue growth [19]. Contrary to our findings, others have found cell-seeded meshes to possess higher tensile strength [12] and increased linear region stiffness [12,32] compared to unseeded synthetic meshes.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This study highlights detailed differences in specific tensile properties between cellseeded and non-cell-seeded scaffolds, with enhanced collagen organization for scaffolds implanted with eMSCs. In agreement with our findings, others have found increased total collagen content for cell-seeded scaffolds following implantation [12,13], with enhanced stimulation of tissue growth [19]. Contrary to our findings, others have found cell-seeded meshes to possess higher tensile strength [12] and increased linear region stiffness [12,32] compared to unseeded synthetic meshes.…”
Section: Discussionsupporting
confidence: 79%
“…For reconstruction of the vagina due to trauma or a congenital defect using a tissue engineering approach, epithelial cells [16,17] and smooth muscle cells [13,16] have been explored. Similarly, repairing damaged vaginal tissue due to POP, vaginal fibroblasts [18], musclederived stem cells [19], and mesenchymal stem cells (MSCs) [14] have been used. MSCs have a particular advantage over differentiated cells, largely due to their ability to control inflammation and encourage repair caused by injury, through complex paracrine immunomodulatory pathways involving both the innate and adaptive immune responses [20].…”
Section: Introductionmentioning
confidence: 99%
“…The present study detected the expression of Sca-1 and Oct4 in cavernous tissue and cells and the results were similar to the findings from non-corpus cavernosum-derived MDSCs reported by Nieponice et al (2008) and Ho et al (2009). The techniques presented in the present study can be used with previously established methods to identify corpus cavernosum stem cells and improve in their identification rate.…”
Section: Discussionsupporting
confidence: 75%
“…This study revealed that the injection of MDSCs into the anal sphincter improved functional properties of fecal incontinence. Furthermore, Ho et al (2009) demonstrated that autologous MDSCs grown on small intestinal submucosa generated SMCs and, upon implantation into a rat model of vaginal defects, stimulated vaginal tissue repair. Thus, autologous MDSCs on scaffolds represent a promising approach for the treatment of vaginal repair.…”
Section: Skeletal Musclementioning
confidence: 98%